BUILDING THE FUTURE OF INDONESIAN EDUCATION FOR ALL: SCHOOL PARTNERSHIP MANAGEMENT IN IMPROVING THE QUALITY OF EDUCATION - Suharman, Suharman; Zamroni, Zamroni; Tamam, Badrut; Khojir, Khojir (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Establishing strong partnerships between educational institutions, school committees, parents, communities and businesses is the main strategy in attracting community involvement to improve the quality of education. Through partnership cooperation, educational institutions are expected to be able to improve the quality of education. This research aims to find out how the planning, organisation, implementation and evaluation carried out by Madrasah Ibtidaiyah Arrahmah Samarinda in improving the quality of education through partnership cooperation. This research uses a qualitative approach with a case study design. As for the results, the first planning of school partnership management in Madrasah Ibtidaiyah Arrahmah Samarinda begins with identifying and analysing the needs of the school. Furthermore, synchronising the curriculum and setting goals. Second, the organisation of school partnership management is carried out by optimising the resources owned by both the school and the partners. Third, the implementation of school partnership activities in improving the quality of education in Madrasah Ibtidaiyah Arrahmah Samarinda, has been done well, this can be seen from the various activities carried out by cooperating with various parties ranging from school committees, teacher communities, parents, government agencies, academic institutions, communities and businesses. Fourth, the evaluation of partnership cooperation is carried out after the implementation of the activity, this is done to find out the support, obstacles, shortcomings and advantages of the programme that has been carried out.